Synthesis and Characterization of Upconversion Photoluminescence Er3+, Yb3+ Co-doped SrMoO4 Particles via Microwave-Assisted Metathetic Route - Sung Lim, Chang (Asian Journal of Chemistry, 2012)
Er3+/Yb3+ co-doped SrMoO4 (SrMoO4:Er3+/Yb3+) particles were successfully synthesized via a cyclic microwave-assisted metathetic route followed by further heat treatment. Well-crystallized SrMoO4:Er3+/Yb3+ particles (100-500 nm) were formed after heat treatment at 600 ºC for 3 h and showed a fine and homogeneous morphology. With excitation at 980 nm, SrMoO4:Er3+/Yb3+# exhibited a strong 525-nm emission band and a weak 550-nm emission band in the green region and a weak 655-nm emission band in the red region. The Raman spectra of SrMoO4:Er3+, SrMoO4:Er3+/Yb3+ and SrMoO4:Er3+/Yb3+# particles indicated additional strong peaks at both higher frequencies (564, 524, 456 and 403 cm-1) and lower frequencies (294, 251 and 220 cm-1).